Probabilistic Assessment Study of Channels Downstream Slopes Erosion in the Maritime Environment - Khalifa, M. A.; Ganainy, M. A. El; Nasr, R. I. (Journal of coastal research, 2009)
This research deals with the probabilistic simulation and assessment of erosion in the downstream maritime slopes in hop ports (ports with deep approach channels to be able to accommodate the recent vessels generations) with natural side slopes. The study concentrated on the liquefaction effect in the erosion factor, which is the main controllable parameter for this phenomena. The probability of failure for the limit state function represents the erosion factor, which has a liable representation by a normal distribution with parameters μ = 2.63 and σ = 1.69, as a representative limit state function. This research deals with a maritime channel with certain dimensions as an example. The probabilistic simulations for downstream slope erosion were carried out using the Monte Carlo technique by using a probabilistic model. The generated probabilistic histograms of the erosion factor based on one run and different numbers of simulated random samples were determined. Based on these reliability simulation results, the erosion volumes per unit width of the channel were evaluated. Validation and sensitivity analyses were also carried out to ensure more reliability for this research. The study produced a group of guiding regression models for estimates and the determined conclusions related to the evaluated erosion volumes we carefully examined by considering calculation conditions based on a 95% confidence level with different assumptions. Then preliminary estimates for the eroded volumes (m3/m) in the downstream slope of the channel were evaluated and so used to determine the relevant regression models. These distributions were determined based on a group of assumed realistic conditions, which include variable berm depths and constant downstream slope angles in one simulated group with erosion volumes against downstream slopes depths heights variation and constant berm depths and variable slope angles in another with erosion volumes against downstream slopes angles variation. The limit state functions representing the erosion volumes variation behavior under the different conditions were also determined by using reliable statistical goodness-of-fit software. The research results are presented in a graphical form for the purpose of improving the current application capabilities in the subject and providing practical usage for the unprotected maritime navigation channel, trenches, and maritime downstream slopes.